Contrasting patterns of prehistoric human diet and subsistence in northernmost Europe - Pääkkönen, Mirva; Blauer, Auli; Olsen, Bjørnar Julius; Evershed, Richard P.; Asplund, Henrik (Scientific Reports, 2018)
Source at https://doi.org/10.1038/s41598-018-19409-8 . Current archaeological evidence indicates the transition from hunting-fishing-gathering to agriculture in Northern Europe was a gradual process. This transition was especially complex in the prehistoric North Fennoscandian landscape where the high latitude posed a challenge to both domestic animal breeding and cereal cultivation. The conditions varied, the coastal dwellers had access to rich marine resources and enjoyed a milder climate due to the Gulf Stream, while those living in the inland Boreal forest zone faced longer and colder winters and less diversity in animal and plant resources. Thus, the coastal area provided more favourable conditions for early agriculture compared to those found inland. Interestingly, a cultural differentiation between these areas is archaeologically visible from the late 2 nd millennium BC onwards. This is most clearly seen in regionally distinct pottery styles, offering unique opportunities to probe diet and subsistence through the organic residues preserved in ceramic vessels. Herein, we integrate the lipid biomarker, compound-specific stable carbon isotopes (δ 13 C), and zooarchaeological evidence to reveal culturally distinct human diets and subsistence patterns. In northern Norway, some of the coastal people adopted dairying as part of their subsistence strategy, while the inhabitants of the interior, in common with northern Finland, continued their hunter-gatherer-fisher lifestyles.